Qualidade das águas e diversidade microbiana do Rio Doce após o rompimento da barragem do Fundão - Cordeiro, Marcelle Candido (2018)
On November 5th, 2015, the Fundão tailing dam, located in Minas Gerais, Brazil, rupture, releasing between 50 and 60 million cubic meters of ore tailing into the Doce River. Samples of water collected in the month of the spill (Nov/2015), after 4 months (Apr/2016) and 9 months later (Sept/2016) were analyzed to investigate possible changes in water quality and microbial diversity resulting from the disaster. The main immediate effect of the disaster on water quality identified was the increase in turbidity levels (on Nov/2015 it was ~ 36 times higher than recommended Brazilian Legislation). In the same period, the group Actinobacteria, a taxon usually associated with soil composition, was increased in relation to Apr/2016 and Sep/2016 and to Paraguaçu River, an environment without mining historic. Nevertheless, 1 year after the disaster, there was an increase of turbidity levels above the water quality legislation, CONAMA 357, and the historical averages in the rainy season on dez/2016 (IGAM public database).